Periodontitis and Intra-Oral Plasmacytosis in a Noonan’s Syndrome Patient - Hadeel Alqatami; Khalid N. Said; Adham A. Ammar; Hani Nazzal (Case Reports in Dentistry)
A 13-year-old female patient with Noonan’s syndrome, intra-oral periodontitis, and associated periodontal lesions is presented in this case report. The patient suffered early onset severe molar pattern periodontitis and recurrent intra-oral inflammatory lesions, pyogenic granuloma, and plasmacytosis, which were excised and controlled using a strict oral hygiene protocol based on long-term use of chlorhexidine-based products as auxiliary aid to regular home care and brushing.